A scoping study of moral injury: Identifying directions for social work research. (November 2016) - Haight, Wendy; Sugrue, Erin; Calhoun, Molly; Black, James
Abstract: This paper presents a scoping study of moral injury that identified directions for social work research. "Moral injury" refers to lasting psychological, spiritual and social harm caused by one's own or others' actions in a high stakes situation that transgress deeply held moral beliefs and expectations. A "scoping study" is a type of systematic review and knowledge synthesis useful when considering complex, emerging areas of research. Results revealed an increasing interest in moral injury over the past five years primarily in psychology/psychiatry. The majority of published articles are conceptual. Empirical studies aim to better understand the experience of moral injury, qualitatively; and develop and evaluate instruments to assess moral injury, quantitatively. Most empirical studies of moral injury involve US war veterans with little attention to moral injury in other groups, sociocultural contexts, or at different times in development. Failure to address issues of moral injury in social work may leave vulnerable clients struggling with issues of guilt, shame, moral confusion, and an absence of meaning that may persist for years and create obstacles to positive change. In addition, social workers may experience moral injury as they witness morally injurious behavior of others and of systems. If unaddressed, such injuries may diminish effectiveness, or lead to burn out. Social workers need relevant research to understand the extent to which moral injury affects them and their clients, and how to identify and address it. Highlights: Moral injury is psychological harm caused by one's own or others' moral transgressions. Research on moral injury has mostly occurred in the military context. Social workers practice in morally complex contexts in which individuals experience moral injury. Social workers need relevant research to understand and address moral injury.